IQOS point-of-sale marketing: a comparison between Arab and Jewish neighborhoods in Israel - Amal Khayat; Hagai Levine; Carla J. Berg; Lorien C. Abroms; Zongshuan Duan; Yan Wang; Cassidy R. LoParco; Daniel Elbaz; Yuxian Cui; Yael Bar-Zeev (BMC, 2024)
Abstract Background Philip Morris International's IQOS, with its heatsticks (HEETS), is the heated tobacco product with the largest global market share. IQOS and/or electronic cigarettes use rate is higher among Arabs vs. Jews in Israel. This paper aims to compare IQOS point-of-sale marketing strategies, and regulatory compliance in Arab vs. Jewish neighborhoods in Israel. Methods We integrated data from two separate studies including a cross-sectional survey with IQOS retailers (December 2020-April 2021) and audits of points-of-sale that sold IQOS/HEETS (April 2021-July 2021) in 5 large cities in Israel, after marketing restrictions including a points-of-sale display ban and plain packaging became effective in Israel (January 2020). The survey included 69 points-of-sale (21 Arab, 48 Jewish neighborhoods) and the audits included 129 points-of-sale (48 Arab, 81 Jewish neighborhoods). Comparisons of IQOS marketing strategies between points-of-sale in Arab and Jewish neighborhoods were conducted using Chi-Square test, Fisher's exact test or Mann-Whitney test, as appropriate. Thematic analysis was used to analyze open-ended questions. Results The survey showed that most marketing strategies, such as promotions to customers, were uniform across points-of-sale in Arab and Jewish neighborhoods. The most noteworthy differences were that a higher proportion of retailers from Arab neighborhoods were invited to IQOS parties (47.6% vs. 21.7%, p < 0.05) and reported personal communication with a Philip Morris International's representative (80.0% vs. 51.2%, p < 0.05). Additionally, Philip Morris International's representatives assisted points-of-sale in both Arab and Jewish neighborhoods in implementing the display ban by providing free compliant cabinets and product placement instructions, and directly interacted with customers. The audits showed that points-of-sale in Arab neighborhoods were more compliant with the display ban (25.5% vs. 8.8%, p < 0.05), but less compliant with plain packaging (62.5% vs. 79.3%, p < 0.05). Conclusions There were not many notable differences in IQOS marketing across points-of-sale in Arab vs. Jewish neighborhoods, but Philip Morris International utilized marketing elements of cultural significance, especially for points-of-sale in Arab neighborhoods, such as more personal communication and invitation to social events. Continuous surveillance of tobacco points-of-sale marketing and legislation compliance is needed, with a special focus on demographic/location-based differences.